Biological Invasions in Conservation Planning: A Global Systematic Review - Mačić, Vesna; Albano, Paolo G.; Almpanidou, Vasiliki; Claudet, Joachim; Corrales, Xavier; Essl, Franz; Evagelopoulos, Athanasios; Giovos, Ioannis; Jimenez, Carlos; Kark, Salit; Marković, Olivera; Mazaris, Antonios D.; et al. (Frontiers in Marine Science, 2018)
Biological invasions threaten biodiversity in terrestrial, freshwater and marine ecosystems, requiring substantial conservation and management efforts. To examine how the conservation planning literature addresses biological invasions and if planning in the marine environment could benefit from experiences in the freshwater and terrestrial systems, we conducted a global systematic review. Out of 1149 scientific articles mentioning both ‘conservation planning’ and ‘alien’ or any of its alternative terms, 70 articles met our selection criteria. Most of the studies were related to the terrestrial environment, while only 10% focused on the marine one. The main conservation targets were species (mostly vertebrates) rather than habitats or ecosystems. Apart from being mentioned, alien species were considered of concern for conservation in only 46% of the cases, while mitigation measures were proposed in only 13% of the cases. The vast majority of the studies (73%) ignored alien species in conservation planning even if their negative impacts were recognized. In 20% of the studies, highly invaded areas were avoided in the planning, while in 6% of the cases such areas were prioritized for conservation. In the latter case, two opposing approaches led to the selection of invaded areas: either alien and native biodiversity were treated equally in setting conservation targets, i.e. alien species were also considered as ecological features requiring protection, or more commonly invaded sites were prioritized for the implementation of management actions to control or eradicate invasive alien species. When the ‘avoid’ approach was followed, in most of the cases highly impacted areas were either excluded or invasive alien species were included in the estimation of a cost function to be minimized. Most of the studies that followed a ‘protect’ or ‘avoid’ approach dealt with terrestrial or freshwater features but in most cases the followed approach could be transferred to the marine environment. Gaps and needs for further research are discussed and we propose an 11-step framework to account for biological invasions into the systematic conservation planning design.